The Influence of Islamic Financial Literacy on The Investment Decisions of Millennials: A Behavioral Finance Approach - Nurchayati Nurchayati (Journal of Islamic Economy, 2025)
The rapid growth of Indonesia’s digital economy and the expansion of Islamic financial services have created new investment opportunities for Muslim millennials. However, low levels of Islamic financial literacy remain a challenge that may affect investment quality and Sharia compliance. This study examines the influence of Islamic financial literacy on the investment decisions of Indonesian millennials. Using a quantitative survey approach, data were collected through purposive sampling involving Muslim millennials aged 25–40 years who have invested or have interest in Sharia-based instruments. A structured questionnaire measured Islamic financial literacy knowledge, understanding of contracts, and Sharia attitudes including investment decision variables, including risk assessment, instrument selection, and investment orientation. Multiple linear regression analysis revealed that Islamic financial literacy has a significant and positive effect on investment decisions. Respondents with higher literacy demonstrated greater prudence, preferred halal instruments such as sukuk and Islamic mutual funds, and avoided speculative assets. These findings highlight the importance of strengthening Islamic financial education, integrating digital Sharia learning, and improving financial platform transparency to support sustainable Sharia investment behavior among millennials